EXPERIMENTAL PHOTOGRAPHY - Gatcum, Chris; Yarham, Rob; Herriott, Luke (London, United Kingdom : AMMONITE PRESS, 2018)
52 Assignments: Experimental Photography is a mission brief, a photographic workshop, a personalised journal, and an anarchic guide to putting the creativity back into your photography. It is filled with prompts and projects, nudges and sparks, innovations and inspirations, and - most importantly - experiments in shooting, processing, and printing, to help you kick your photographic habits, step out of your comfort zone and create your own collection of experimental work. The book features 52 colour-coded commissions and concepts with alternative ideas for composing, creating and printing photographic images. You will be briefed to tackle modern uses for traditional film (hacking vintage film cameras, making pinholes, playing with plastic, collecting the filters that inspired Instagram) and traditional uses for digital (multiple exposures, extreme speeds, timed challenges, focus tricks), as well as lo-tech and hi-tech ways to manipulate your prints (staining prints with water, digital effects, photocopy prints, burning photos, printing on flexible surfaces). The rest of the journal's pages are styled for you to add your own thoughts, notes, lists, Top 10s, technical specifications, quotes, and even sketches and doodles, creating a record of your own 52 photographic assignments. These may be completed weekend by weekend over the course of a year, or dipped into every time you need to bring a new edge or experimental approach to your photography. AUTHOR: Chris Gatcum is an award-winning photographer, and a highly experienced writer and editor of technical and technique-based photography books and articles. His published titles include The Complete Book of Photography and Plastic Cameras (Ammonite Press). SALES POINTS: . 52 colour-coded commissions and concepts to get you experimenting with your photography . Experimental projects include: pinhole cameras, staining prints with water, burning photos, printing on flexible surfaces . With space to fill with your own notes, ideas, plans and sketches 60 colour photographs and 10 illustrations.
Includes index.
Keywords: Photography -- Technique; Photography -- Special effects